REPRESENTASI GAYA HIDUP MODERN DALAM IKLAN GOJEK INDONESIA VERSI HIDUP TANPA BATAS ITU APA SIH - Trinata Pardede; Chelsy Yesicha (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
Modernity and practicality cannot be separated from modern society. A dynamic life, open to technology, prioritizing timeliness, not bothering to be the idea of forming an online transportation mode known as go-jek. All the complexities of the problems of modern society are answered through the go-jek application service, which is summarized in the Go-jek Indonesia advertisement for Life Without Limits. Go-jek ads offer changes using the go-jek application on smartphones to meet needs that are accommodated through one application. With the help of go-jek, service users can enjoy life without limits. The purpose of this study was to find out the level of reality, representation and ideology of modern lifestyles depicted in the Go-jek Indonesia advertisement for the Life Without Borders What Is It?The method used in this study is qualitative with a semiotic analysis unit from John Fiske. The subjects and objects in this study were observations and analyzes of the appearance of audio, visuals and representations of modern lifestyles in each scene from the Go-jek Indonesia ad version of the Life Without Limits What Is It? Data collection techniques used are observation, documentation and literature.The results of the study show that at the level of reality, the modern lifestyle in this advertisement is seen in aspects of appearance, and environment. Attractive appearance adds confidence, conveying the impression of being smart, expert and ethical, while in the environmental aspects go-jek wants to touch urban communities that deal with distance and time. At the level of representation, modern lifestyles are displayed with a background of dense shots, sound with a fast tempo, wanting to show the complexity of identical modern societies racing against time. At the level of ideology, modern lifestyles describe two ideologies namely class ideology and consumerism. This social class is characterized by a high level of education, income and has a high appreciation for hard work, and future planning, while the consumerism ideology describes a modern society that likes to consume modern lifestyle trends, does not want to be outdated and always follows new lifestyle trends.